1990
DOI: 10.1029/ja095ia08p12209
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of an artificial electron beam with the Earth's upper atmosphere: Effects on spacecraft charging and the near‐plasma environment

Abstract: The ionization created in the Earth's upper atmosphere by an electron beam emitted from a low altitude spacecraft is described by two coupled nonlinear differential electron transport equations for the up‐going (along a magnetic field line) and down‐going differential energy flux. The equations are solved numerically, using the mass spectrometer and incoherent scatter data (MSIS) atmospheric model and the international reference ionosphere (IRI) model, yelding estimates of the differential electron energy flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…It is expected that at beam energies below a few keV, for the conditions modeled here, that the BAI will dominate over the BPI. This is consistent with conclusions reached from sounding rocket observations of return current measurements during beam ejection [Neubert et al, 1990]. Here it was found that BAI-induced fluxes, together with "passive" currents from the ambient ionosphere, could account for the observed currents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is expected that at beam energies below a few keV, for the conditions modeled here, that the BAI will dominate over the BPI. This is consistent with conclusions reached from sounding rocket observations of return current measurements during beam ejection [Neubert et al, 1990]. Here it was found that BAI-induced fluxes, together with "passive" currents from the ambient ionosphere, could account for the observed currents.…”
Section: Discussionsupporting
confidence: 91%
“…In BPI the beam drives plasma wave modes and subsequent scattering of beam electrons and heating of the ambient plasma. The high-resolution measurements of wave and particle spectra taken in the last decade from the space shuttle [Gurnett et al, 1986;Oberhardt et al, 1993] Paper number 93GL01981 0094-8534/93/93 GL-01981 $03.00 with the ambient neutral atmosphere, the beam-atmosphere interaction (BAI) [Neubert et al, 1990] and to the case of elastic scattering of beam electrons by short-scale Langmuir turbulence in the beam. This choice was motivated by the observations of PEE events mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The present treatment of the electron beam furthermore does not consider energy loss and scattering due to excitation of ELF and VLF waves interactions and spacecraft charging [e.g., Neubert et al, 1986;Neubert and Gilchrist, 2002]. Although these effects have been shown to be less pronounced for MeV beams than for keV beams used in the past, they still need to be quantified.…”
Section: Model Caveats For Beam Propagationmentioning
confidence: 99%
“…This can only happen if the active component of electron current increases. Since the active current component increases with decreasing altitude it was suggested by Neubert et al (1990b) that the active component was due to ionization created in a BAI process. In order to quantify the increased current due to this process, a computer code, first developed for the&tudy of the generation and transport of photoelectrons in the upper atmosphere (Banks and Nagy, 1970) and later for aurora1 electron fluxes (Banks ef al., 1974), was modified by Neubert ef al.…”
Section: Fig 5 Charge-2 Obswations Of M Iei-hbr M Beam Current Ratimentioning
confidence: 99%
“…For the purpose of studying the effect of BAI on charging levels and return current collection of space craft, the CHARGE-2 sounding rocket experiment was the first to allow separate me~u~ment of the active and the passive component of the return current (Neubert et al, 1990b). The experimental configuration is shown in Fig.…”
Section: Andwm-atmosphere Interactionsmentioning
confidence: 99%